Optimalisasi Kemampuan Berfikir Kritis Siswa pada Mata Pelajaran Sejarah Kebudayaan Islam di Madrasah Ibtidaiyah Mambaul Ulum Kota Jambi - Wulandari; Sri Yulia Sari; Rhesti Laila Ulfa (Jurnal Pustaka Cendekia Pendidikan, 2025)
This study discusses "Optimizing Students' Critical Thinking Skills in the Subject of Islamic Cultural History at Mamba Ul Ulum Elementary Madrasah, Jambi City". This study aims to determine how to optimize students' critical thinking skills in learning Islamic cultural history, especially in class V at Madrasah Ibtidaiyah Mambaul Ulum Jambi and what are the obstacles faced by teachers and what are the teacher's strategies in optimizing students' critical thinking skills in the subject of Islamic cultural history. The researcher also explains how teachers at Madrasah Ibtiadiyah Manbaul Ulum, Jambi City, try to realize the learning process so that students actively develop their critical thinking potential. Teachers Apply Critical Thinking Skills, So That Students Are Able to Receive and Analyze Knowledge Critically And explain what are the Factors that influence students' critical thinking skills that cause researchers to be interested in researching students at the Jambi City Elementary School In this study, researchers used the theory of Sanjaya, 2016) to answer the formulation of the problem in this study, namely there are three ways to find out how to optimize critical thinking, the first is How are Students' Critical Thinking Skills in learning Islamic Cultural History for class V at the Mambaul Ulum Jambi Elementary School